Model Komunikasi Program Bale Berdaya Dalam Pengembangan UMKM Binaan Di Kabupaten Sumbawa - Lina Fitriani; Aka Kurnia SF (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the mentoring communication model in the Bale Berdaya Program on the development of assisted MSMEs in Sumbawa Regency. The Bale Berdaya Program is an MSME empowerment initiative implemented by PT Amman Mineral Nusa Tenggara through training, coaching, and business mentoring activities. This research uses a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. The findings show that the mentoring communication model is carried out in a flexible, persuasive, and participatory manner. Mentors act as facilitators, motivators, and information providers in supporting MSME development. Message delivery is conducted through training sessions, discussions, and mentoring activities tailored to the needs of MSME actors. Based on David K. Berlo’s SMCR theory, communication effectiveness is influenced by the communicator’s ability, the selection of communication channels, and the adaptation of messages to receiver characteristics. This communication model plays an important role in enhancing MSME knowledge, motivation, and capacity for sustainable business development.